Impact of the Perceived Quality of Traditional Villages’ Cultural Landscapes on Tourists’ Loyalty - SHEN, Huaheng; AZIZ, Nor Fadzila; HUANG, Menglan; YU, Lingyun (Journal of Environmental Management and Tourism; Vol 14 No 7 (2023): JEMT, Volume XIV, Issue 7(71), Winter 2023DO - 10.14505/jemt.v14.7(71).04, 2023)
This study explored the relationship between the perceived quality of cultural landscapes and tourists’ loyalty to traditional villages using structural equation modeling (SEM) by collecting data from 463 tourists in Huangdu Dong Village within China’s Hunan Province. The results reveal that the perceived quality of traditional villages’ cultural landscapes indirectly and significantly affected tourist loyalty; its influence was primarily transmitted through the mediating variable of tourist satisfaction. Meanwhile, no significant difference in loyalty was observed between tourists’ gender, occupation, and place of residence, while age, educational background, and income level had significant effects on loyalty. This study reveals the importance of cultural landscapes in traditional village tourism and provides important ideas for traditional village tourism marketing. In doing so, this study enhances the competitiveness and influence of traditional village tourism and provides theoretical contributions to sustainable village development.